Perception of car Drivers toward Safety Cyclist Using ADAS - NURFITRI IZZATY,; KAMARUDIN AMBAK, (Recent Trends in Civil Engineering and Built Environment, 2022)
The lack of safety towards cyclist has been highlighted due to road crash statistic in Malaysia. By using the technology of Advanced Driver Assistance System (ADAS), this study can help to improve the safety of cyclist in future. This study was conducted to determine the level of consumer acceptance on the idea of technology Advanced Driver Assistant System (ADAS) installation based on the Technology Acceptance Model (TAM). The objective of this study is to identify the factors that influence the perception of car drivers toward cyclist and determine the acceptance of car drivers using ADAS based on TAM. The study area is in around Putrajaya and the questionnaire was conducted and distributed among 200 respondents via google form in the study area. The questionnaire was design based on Technology Acceptance Model (TAM) by doing a survey online due covid-19 pandemic. The Regression and Correlation analysis were used for this study and the analysis were significant for acceptance of ADAS. The result of this study shows that the dominant factor of TAM contributing to the installation of Advanced Driver Assistance System (ADAS). Among the opinions to install the system of ADAS is that the system helps to increase the safety in driving and reduce the amount of accident.